THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, COMPANY SIZE AND CAPITAL INTENSITY ON TAX AVOIDANCE: (Empirical Study on Property and Real Estate Building Construction Sector Companies Listed on the Indonesia Stock Exchange in 2015-2020) - Mutiara Siregar; Khoirunisa Azzahra (Transpublika Publisher, 2022)
This study aims to examine the effect of corporate social responsibility, company size and capital intensity on tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange in 2015-2020. The sampling technique used was purposive sampling and 23 companies were included with a period of 6 years so that 138 samples were observed. The analytical method used to examine the effect of corporate social responsibility on tax avoidance is the model with the help of software reviews version 10. The results show that corporate social responsibility, company size has an effect on tax avoidance and conversely capital intensity has no significant effect on tax avoidance. There are still many companies that have not disclosed their financial statements in full company management activities, so it is hoped that the company can publish its financial statements in full because it is not only beneficial for the company, this can also increase public trust in the company.